PENERAPAN HUKUM TERHADAP ANAK YANG MELAKUKAN ABORTUS DIKAITKAN DENGAN PASAL 49 AYAT 2 KUHP. - Tina Asmarawati (SUPREMASI HUKUM, 2022)
Today there is a lot of sexual violence against minors. A religious teacher as well as a scout and paskibraka trainer at SMPN Tangerang molested his students and the victim received trauma healing services for his psychic healing. If a child commits a crime, it is regulated under Law Number 11 of 2012 concerning the Juvenile Justice System. Imprisonment for children is only used as a last resort (ultimum remedium). The issue of abortion is regulated in Article 346 of the Criminal Code, namely that a woman intentionally causes the abortion or death of her womb or orders someone else to cause the perpetrator to be sentenced to a maximum imprisonment of four years divided by two. The author considers it important to examine this issue because children are the younger generation who must receive special protection. Problem Formulation How is the application of the law to children who have abortions? Can the crime of abortion committed by children be categorized into Article 49 paragraph 2 of the Criminal Code. Objectives and Uses of Theoretical Research is expected to provide benefits and expand thinking on the development of legal science in the field of Criminal Law, especially in the crime of abortion due to rape. The method that the author uses in this research is normative juridical. In conclusion, children who have an abortion due to rape can be categorized into article 49 paragraph 2 of the Criminal Code. (noodweer exces) into forgiving reasons (fait d'axcuse) because it eliminates the element of guilt of the criminal offender. Keywords: Rape; child; abortion